Policy Analysis of the Role of Nurses in Implementing Inpatient Patient Safety at the Muhamadiyah Hospital in Bandung - Yulianti Yulianti; Agus Alamsyah (Penerbit Jurnal Indonesia, 2023)
Objective_This study aims to determine the policy role of nurses in implementing inpatient safety at Muhammadiyah Bandung Hospital, to determine policies and inhibiting factors in implementing patient safety and to find solutions to obstacles in implementing patient safety. Design/Method_Researchers in this study used a qualitative descriptive research method, namely by understand the phenomenon that occurs by describing it in the form of words and language that is specific and natural. the role of nurses in implementing inpatient safety at Muhamadiyah Hospital Bandung. Originality_this research is the first research conducted at Muhamdiyah Hospital Bandung. research both interview activities and patient safety implementation activities